Introduction - Babro, R. J.; Romer, P. M. (Quarterly Journal of Economics, 1991)
Journal Article Introduction Get access Robert J. Babro, Robert J. Babro Search for other works by this author on: Oxford Academic Google Scholar Paul M. Romer Paul M. Romer Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 106, Issue 2, May 1991, Page i, https://doi.org/10.1093/qje/106.2.i Published: 01 May 1991